Interface Engineering of 2D/3D Perovskite Heterojunction Improves Photovoltaic Efficiency and Stability. Issue 5 (18th March 2021) - Ji, Chao; Liang, Chunjun; Song, Qi; Gong, Hongkang; Liu, Ning; You, Fangtian; Li, Dan; He, Zhiqun
Abstract : The instability of 3D perovskite and the low power conversion efficiency (PCE) of 2D perovskite limit the development of perovskite solar cells (PSCs). Using 2D perovskite to passivate 3D perovskite thin films by heterojunction engineering has become an effective strategy to develop stable and efficient PSCs. Therefore, it is important to find suitable 2D perovskite passivation materials. Herein, a 2D/3D heterojunction perovskite is formed in situ by introducing a long‐chain alkyl phenylbutylammonium (PBA + ) cation. The 2D perovskite has the property of n  = 2, which passivates the surface defects of the 3D perovskite, resulting in enhanced photoluminescence intensity and prolonged carrier lifetime. Moreover, the 2D layer changes the interface contact and energy‐level arrangement, making it a more n‐type semiconductor, which facilitates the electron transfer between perovskites and electron transport. This strategy significantly improves the open circuit voltage ( V oc ) and fill factor (FF) of the devices without sacrificing current, and the PCE is improved from 19.22% to 21.76%. The hydrophobic PBA + ‐based 2D layer also improves the humidity stability of the films and enhances the working stability of the device. The PCE of the champion heterojunction perovskite device remains 87% of its initial value after illumination for 1000 h. The results show that heterojunction engineering plays an important role in the preparation of efficient and stable PSCs. Abstract : 2D/3D heterojunction perovskite is formed in situ by introducing a long‐chain alkyl phenylbutylammonium (PBA + ) cation. The surface passivation leads to the reduction of the reverse saturation current of the diode by four orders of magnitude. As a result, open circuit voltage ( V oc ) and fill factor (FF) are significantly improved, and the stability of the device is also greatly improved.